تأثير التجمد على الصخور - خضور, عدنان; أسطة, رامي; نصور, ماهر سجيع (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير التجمد في الصخور الكربوناتية المأخوذة من مقالع محددة في المنطقة الساحلية من سوريا وذلك بوساطة اختبار الأصالة (Soundness Test) باستخدام سلفات الصوديوم, و إمكانية وجود ارتباط بين تجربة الاهتراء (لوس أنجلوس) واختبار الأصالة. نتيجة البحث: - أغلبية الصخور المدروسة من المقالع المختلفة هي مقاومة لتأثير التجمد . - ارتباط بعض الخصائص الفيزيائية للصخر باختبار الأصالة باستخدام سلفات الصوديوم. - هناك علاقة تربط اختبار الاهتراء (لوس أنجلوس ) واختبار الأصالة باستخدام سلفات الصوديوم لكن بشروط محددة . The aim of this research is to study the influence of freezing on carbonate rocks extracted from specific quarries in the coastal region of Syria, and the possibility of finding the correlation between Abrasion test (L.A) and Soundness test, using Sodium Sulfate. The results or findings of this research are as follows: - Most of the carbonate rocks studied freezing-resistant. - There are correlations between some physical properties of carbonate rocks and Soundness test, using Sodium Sulfate but displaying different ratios. - There is a relationship between Abrasion test (L.A) and Soundness test, using Sodium Sulfate but under specific conditions.